Investigating Students’ Mindset in Learning English at SMPN 2 Lubuk Pakam - Kirana, Alvira (Universitas Negeri Medan, 2025)
This study investigates the mindset of junior high school students in learning English and the factors influencing its development. Conducted at SMPN 2 Lubuk Pakam with 22 students from class VIII-9, the research employed a qualitative approach using open-ended questionnaires and thematic analysis. Referring to Dweck’s (2006) six mindset aspects; challenges, obstacles, effort, criticism, success of others, and self- perception, the findings show that most students leaned toward a fixed mindset, except in the aspect of criticism, where many showed openness. The study also found that personal experience was the most significant factor shaping students’ mindsets. Positive experiences supported a growth mindset, while negative ones reinforced a fixed mindset. These results highlight the importance of both internal and external support in fostering a growth mindset in English learning. The scope of this study includes six aspects of mindset as proposed by Dweck (2006): challenges, obstacles, effort, criticism, success of others, and self-perception of ability. In addition, it explores three influencing factors: social environment, personal experience, and cultural values.social environment, personal experience, and cultural values. Main Terms Defined: Growth Mindset: The belief that abilities can be developed through effort, hard work, and dedication. Fixed Mindset: The belief that abilities are fixed and cannot be changed.